1969
DOI: 10.1073/pnas.62.4.1129
|View full text |Cite
|
Sign up to set email alerts
|

Solubilization of Particulate Proteins and Nonelectrolytes by Chaotropic Agents

Abstract: Abstract.-Chaotropic ions (those ions which favor the transfer of apolar groups to water) provide a highly effective means for the resolution of membranes and multicomponent enzymes and for increasing the water solubility of particulate proteins and nonelectrolytes. The action of chaotropic agents is related to their effect on the structure and lipophilicity of water.The meager water solubility of particulate proteins and many biological compounds such as hemes, purines and pyrimidines, nucleosides, certain vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
162
0

Year Published

1975
1975
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(168 citation statements)
references
References 12 publications
6
162
0
Order By: Relevance
“…The variation in results from one detergent extract to another can be explained on the basis of differential solubilization and inactivation of various proteins in different detergents. For example, it is known that different chaotropic salts have wide ranges of effectiveness: potassium thocyanate releases only small portions of proteins from erythrocyte ghosts [5], guanidine hydrochloride releases all except one or two erythrocyte membrane proteins [19], and LIS brings about complete dissolution of the membrane [13]. However, use of these protein perturbants or chaotropic agents, which are weaker than detergents, does not lead to solubilization of proteins that are more strongly bound to the lipid matrix of the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The variation in results from one detergent extract to another can be explained on the basis of differential solubilization and inactivation of various proteins in different detergents. For example, it is known that different chaotropic salts have wide ranges of effectiveness: potassium thocyanate releases only small portions of proteins from erythrocyte ghosts [5], guanidine hydrochloride releases all except one or two erythrocyte membrane proteins [19], and LIS brings about complete dissolution of the membrane [13]. However, use of these protein perturbants or chaotropic agents, which are weaker than detergents, does not lead to solubilization of proteins that are more strongly bound to the lipid matrix of the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought to be primarily the result of their ability to disrupt the hydrogen -bonded structure of water whereby the hydrophobicity of the aqueous solvent is increased [5].…”
Section: 14)mentioning
confidence: 99%
“…Bicarbonate in pancreatic juice and duodenal fluids neutralizes gastric acid and pro-vides an optimal pH environment for digestive enzymes to function properly in the duodenum (Lee and Muallem 2008). In addition, as a moderate chaotropic ion, bicarbonate facilitates the solubilization of macromolecules such as mucins (Hatefi and Hanstein 1969). Recent studies suggest that the abnormal bicarbonate secretion observed in cystic fibrosis (CF) leads to altered mucin hydration and solubilization (Quinton 2010), resulting in hyperviscous mucus that blocks ductal structures of the lung and pancreas (Quinton 2001(Quinton , 2008.…”
Section: Many Cystic Fibrosis Transmembrane Conductance Regulator (Cfmentioning
confidence: 99%